Quale posto per il passato nella città? Narrazioni e pratiche di recupero nella città vecchia di Taranto - Vincenzo Luca Lo Re (Archivio Antropologico Mediterraneo)
This contribution results from ethnographic research on the reuse practices of abandoned spaces, conducted between 2019 and 2021 in the context of the old city of Taranto, a historic urban centre characterised by depopulation phenomena and a long history of settlement and sedimentation of meanings and practices. The work focuses on the relationship between urban regeneration processes, which promote the transformation and re-signification of abandoned urban spaces, and the experience that inhabitants and social groups reproduce in the narratives of the neighbourhood space through reuse and revisitation from below. This relationship reveals an articulated tension that reflects, on the one hand, the need to find new solutions to the environmental crisis caused by the steel industry (ILVA - Arcelor Mittal) and, on the other, the possibility of rethinking the economy and management of urban spaces to capitalise and re-exploiting a marginalised territory that is now once again central. The relationship between remembrance and oblivion represents a central issue for understanding what meanings and position the old city is taking on and through which practices we attempt to construct new narratives and new experiences of reuse.